A novel energizing strategy for a grid-connected modular multilevel converter operating as static synchronous compensator. (July 2019) - Duarte, Samuel N.; de Almeida, Pedro M.; Barbosa, Pedro G.
Highlights: Energizing strategy of grid-connected modular multilevel converter. Control algorithm to charge the DC capacitor of a voltage source converter connected to mains. Limit inrush current of FACTS and VSC-HVDC based converter. Abstract: This paper proposes a novel energizing strategy for a three-phase modular multilevel converter connected to the electric network as static synchronous compensator. The energizing system is comprised of two thyristors and its controller. A comprehensive mathematical model is developed for each energizing stage. Based on the models, a control law is designed in order to compute the thyristors firing angle. This is performed in such a way that the maximum value of the energizing current drained from the grid is limited. First, during the positive half-cycle of the mains voltage, the current flows through two arms of the modular converter charging its DC capacitors. In the following half-cycles, the pre-charged capacitors transfer part of their stored energy to the other arms capacitors. The process is repeated until the total DC voltage of the modular converter reaches the grid voltage peak value. Digital simulation results are presented to validate the proposed methodology.